2015
DOI: 10.1111/acem.12643
|View full text |Cite
|
Sign up to set email alerts
|

Intraarrest Rhythms and Rhythm Conversion in Asphyxial Cardiac Arrest

Abstract: Objectives:The objective was to analyze the cardiac arrest rhythms presenting during asphyxial cardiac arrest (ACA).Methods: Asphyxial cardiac arrest was induced in 30 Landrace large white piglets, aged 12 to 15 weeks and with a mean (AESD) weight of 20 (AE2) kg. After the onset of cardiac arrest, the animals were left untreated for 4 minutes, after which cardiopulmonary resuscitation was commenced. Heart rhythms were monitored from the onset of asphyxia until return of spontaneous circulation or death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…VFCA was chosen as a control group. However, a recent experimental study demonstrated that even in ACA there is significant intra-arrest rhythm conversion and that around 70% of the animals exposed to endotracheal clamping at some point during the experiment convert to VF 23 . This experimental study may explain the heterogeneity in the metabolomic profile in some of our animals.…”
Section: Discussionmentioning
confidence: 98%
“…VFCA was chosen as a control group. However, a recent experimental study demonstrated that even in ACA there is significant intra-arrest rhythm conversion and that around 70% of the animals exposed to endotracheal clamping at some point during the experiment convert to VF 23 . This experimental study may explain the heterogeneity in the metabolomic profile in some of our animals.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, asphyxial cardiac arrest is characterized by a prolonged time course and an important pre-arrest period where hypoxia and hypercapnia progressively advance along with maintained but gradually deteriorating cardiopulmonary function [ 6 , 32 ]. During the asphyxial interval, general de-energization and mitochondrial complexes inactivation take place in parallel with oxygen shortage, eventually resulting in complete decompensation and a higher degree of energy depletion compared with dysrhythmic cardiac arrest [ 7 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These indicate a preserved stressed volume and that the endogenous catecholamines seem sufficient for achieving ROSC [ 51 ]. Based on the findings of the present and other studies [ 48 , 50 52 ], the inadequacy of global hemodynamic parameters to monitor tissue perfusion and oxygenation [ 53 ], and the significant possibility for spontaneous conversion of a non-shockable rhythm to a shockable one during the asphyxial cardiac arrest interval [ 33 ], the recommendation for administration of adrenaline as soon as possible in asphyxial cardiac arrest with a non-shockable rhythm should be critically re-evaluated, while Pmcf must be further studied as a new prognostic parameter for ROSC regardless of the cause of arrest.…”
Section: Discussionmentioning
confidence: 99%
“…In OHCA patients with a non-cardiac medical origin with an initial non-shockable rhythm, conversion to shockable rhythm was not associated with good neurologic outcomes. Varvarousi et al reported that the conversion group showed lower ROSC rate than the non-conversion group in an animal asphyxial cardiac arrest study [22].…”
Section: Discussionmentioning
confidence: 99%